Adverse mental health and educational outcomes in offspring of parents with mental health problems - Yaya, Getinet Ayano (Curtin University, 2021)
This thesis investigated the risk of psychiatric disorders and symptoms and adverse educational outcomes in offspring of parents with mental health problems. The data for this thesis came from both primary (longitudinal birth cohort data) and secondary (published studies). Findings suggested that, after adjusting for potential confounders, parental mental health problems were associated with increased risk of a wide range of mental health problems in the offspring during childhood, adolescence, and young adulthood.